Ecology of Listeria monocytogenes and Listeria species in India: the occurrence, resistance to biocides, genomic landscape and biocontrol. (24th October 2021) - Barbuddhe, Sukhadeo Baliram; Rawool, Deepak Bhiwa; Doijad, Swapnil Prakash; Vergis, Jess; Malik, Satyaveer Singh; Chakraborty, Trinad
Summary: Listeria monocytogenes, the causative agent of listeriosis, has been implicated in increasing foodborne outbreaks worldwide. The disease is manifested in various forms ranging from severe sepsis in immune‐compromised individuals, febrile gastroenteritis, still birth, abortions and meningoencephalitis. In India, data from studies on the detection and molecular epidemiological analysis of L. monocytogenes are only recently emerging. The presence of Listeria in different ecological niches has been recorded from India, including foods, soil, vegetables, mangrove swamps, seafood, freshwater fishes, clinical cases, and also insects. The organism has also been isolated from women with spontaneous abortions, miscarriage or recurrent obstetric history, aborted foetuses, animal clinical cases and wildlife samples. A novel species of Listeria has also been characterized. Listeria monocytogenes strains isolated from clinical, environmental, and foods showed biofilm‐forming abilities. Listeria monocytogenes serotype 4b isolates of ST328, a predominant and unique ST observed in India, was repeatedly isolated from different sources, times, and geographical locations. Here, we reviewed the occurrence of Listeria in different sources in India, its resistance to biocides, and provide epidemiological analysis on its genomic landscape.